Lean marketing: application of the lean six sigma to marketing: case study - Sá, José Carlos (2022)
The main objective of this work is to implement tools capable of improving the efficiency of production and internal management with a view to improving customer service. To do so, it is necessary to analyze the current processes, identify the points that can be improved and only then adopt the solutions that best serve the objectives to be achieved. As methodology, we elaborated an application plan in a metal-mechanic company that aimed to study the processes related to marketing and the relationship with the clients of this company. In this way, we verified the applicability of Lean Six Sigma for improvements in marketing and customer relationship. Of the most relevant aspects of the work that allowed us to analyze the current functioning of the company, we highlight the creation of a questionnaire for customers. From the analysis, it was possible to verify the weak points of the processes and of the relationship with customers, which allowed the adoption and implementation of tools proposed by the Lean Six Sigma philosophies. The tools, namely CRM, daily meetings (Daily Kaizen) among others, allowed improving the internal communication between the various departments and aspects such as the time between the contact with the client and the preparation of proposals.